- Berbahasa di Dunia Maya: Diglosia Bahasa Anak Muda Sebagai Media Pembelajaran Bahasa Inggris : - - Jaya, Made Suardika; Putra, I Putu Ambara (Journal of Education Reseach and Evaluation, 2025)
In this digital space, language practices no longer strictly adhere to existing conventional norms. The younger generation actively utilizes social media platforms and creates new variations in language practices. This study aims to analyze the diglossia phenomenon in youth communication in the digital realm, particularly on social media. This study applies a descriptive qualitative approach with a content analysis method to data obtained from social media platforms X (Twitter) and Facebook. Data collection techniques include observation, interviews, and documentation. Data analysis techniques use descriptive qualitative analysis. The study results show the practice of digital diglossia among young people, which can be observed through standard and non-standard language, the use of slang, code mixing, and the inclusion of visual symbols (emojis and memes). This language variety can indicate social closeness, group identity, and adaptation to online community norms, effectively contributing to learning English through social media. It is concluded that social media has become a broad space for the practice of diglossia, which is very dynamic and flexible. It has become an effective source of English learning in today's modern era. The implications of the research show that the phenomenon of dual language use by adolescents, especially in the digital realm, can be utilized as an authentic and contextual learning resource.